Cost-Effectiveness of Sequential Denosumab/Zoledronic Acid Compared With Zoledronic Acid Monotherapy for Postmenopausal Osteoporotic Women in China - You, Ruxu; Liu, Jinyu; Ke, Lei; Wan, Min; Zhang, Yu; Yu, Guangyi; Mori, Takahiro (Frontiers in Pharmacology, 2022)
Objective: The primary purpose of this study was to estimate the cost-effectiveness of sequential denosumab/zoledronic acid versus zoledronic acid monotherapy for postmenopausal osteoporotic women in China. Methods: We updated and utilized a previously validated Markov microsimulation model to obtain the cost-effectiveness of two strategies for treating postmenopausal osteoporotic women. We compared the incremental cost-effectiveness ratios (ICERs) (US dollars [$] per quality-adjusted life year [QALY]) of sequential denosumab/zoledronic acid (i.e., biannual subcutaneous denosumab for 3 years followed by annual intravenous zoledronic acid for 3 years) with zoledronic acid monotherapy for 3 years in Chinese women with postmenopausal osteoporosis at ages 65, 70, 75, and 80 from the health care payer perspective. Our study's willingness-to-pay (WTP) threshold was set to three times the value of China's per capita GDP in 2020 ($31,512). Results: The ICERs of sequential denosumab/zoledronic acid versus zoledronic acid monotherapy were $59,389/QALY, $23,821/QALY, $22,710/QALY, and $14027/QALY at age 65, 70, 75, and 80 years, respectively. One-way sensitivity analyses showed that the most impactful parameter was the persistence rate of the medications. If the persistence rate of denosumab or zoledronic acid was increased by 10%, sequential denosumab/zoledronic acid would be cost-effective at age 65. In probabilistic sensitivity analyses, the probabilities of sequential denosumab/zoledronic being cost-effective compared to zoledronic acid monotherapy were approximately 29.3%, 68.7%, 86.1%, and 99.4% for ages 65, 70, 75, and 80 years, respectively, at the WTP threshold of $31,512/QALY. Conclusions: Among Chinese postmenopausal osteoporosis women over 70 years old, sequential denosumab/zoledronic acid was cost-effective compared with zoledronic acid monotherapy at the pre-determined WTP threshold.